Facile Synthesis, Antimicrobial Activity and Molecular Docking of Novel 2, 4, 5‐Trisubstituted‐1H‐Imidazole–Triazole Hybrid Compounds. (6th August 2019) - Chauhan, Sunil; Verma, Vikas; Kumar, Devinder; Kumar, Ashwani
Abstract : Abstract : In the present work, a series of 18 imidazole–triazole hybrids (4a–r ) has been synthesized in good yield from substituted naphthaldehydes and 1, 2‐diketones in the presence of ammonium acetate. The synthesized imidazole–triazole hybrid compounds were characterized by spectral techniques and screened in vitro for their antimicrobial activity. Compound4h was found to be most active against Staphylococcus epidermidis, and compound4e exhibited promising activity against Escherichia coli . In the fungal species under test, compound4q was most potent against Aspergillus niger, even better than the fluconazole. Further, compound4e was docked in the binding site of DNA gyrase topoisomerase II of E. coli .